THE SYSTEMATIC REVIEW OF THE ASSOCIATION OF PREGNANCY OUTCOMES AND CHRONIC KIDNEY DISEASE - Supriyadi, Agung; Andimapali, Zulfikar; Fitria, Adina; Whisnu Dewanegara, Rahadiyan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Pregnancy as a metabolic stress test that might reveal underlying endothelial dysfunction and vascular illness. Maternal cardiovascular disease risk is heightened in cases of adverse pregnancy outcomes, including hypertensive disorders of pregnancy, gestational diabetes, and premature birth. Aims : This systematic review is to review the association of chronic kidney disease to its outcomes at pregnant women. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 661 articles, whereas the results of our search on SCIENCE DIRECT brought up 3.6314 articles. The results of the search conducted for the last year of 2014 yielded a total 12 articles for PubMed and 96 articles for SCIENCE DIRECT. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SCIENCE DIRECT. We included five research that met the criteria. Conclusion: In summary, an increased risk of chronic kidney disease was linked to exposure to unfavorable pregnancy outcomes, such as hypertensive disorders of pregnancy, gestational diabetes, and premature birth. Preeclamptic women had the highest chance of developing ESKD. To identify women who are more likely to develop kidney disease, especially following hypertensive disorders during pregnancy, a systematic strategy may be necessary to maximize the patients' long-term follow-up.